Customer Engagement Mediates the Effect of Content marketing on Purchase Intention - Rizkia, Arina Raudhatul; Akbar, Mohammad Aldrin; Lina, Ros (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study examines the effect of Content Marketing on Purchase Intention through Customer Engagement. Research Design and Methodology: This study uses a quantitative research design with survey and path analysis methods. Data was collected from respondents who were involved in digital interactions with marketing content. Findings and Discussion: The results showed that Content Marketing significantly indirectly affects one's Purchase Intention through increased Customer Engagement. This finding indicates that relevant, engaging, and valuable content can increase consumer engagement, strengthening their intention to purchase. Implications: This research highlights the importance of companies developing content marketing strategies that focus on increasing customer engagement to maximize purchase intention. This research contributes to the digital marketing literature by highlighting the mediating role of Customer Engagement. However, limitations of this study include a sample that may not be representative of the broader population and a cross-sectional design that cannot identify changes in consumer behavior over time. Future research should use a longitudinal design and expand the sample to increase external validity and explore other factors influencing this relationship.